2016
DOI: 10.1177/1471301216682602
|View full text |Cite
|
Sign up to set email alerts
|

The family’s experience and perception of phases and roles in the progression of dementia: An explorative, interview-based study

Abstract: This paper examines how the relatives of a person with dementia experience challenges in everyday life. A model of phases is developed on the basis of interviews with 14 relatives from eight families. Data were subjected to a thematic content analysis, which found that the progression of dementia - from the perspective of the family - had three phases. These phases involved small changes in everyday life, adaptations to everyday life, and the loss of everyday life. The analysis further identified the following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…Their perspectives are more in line with those of the professionals involved. This is in line with the work of Clemmensen et al 39 who found differences between the ‘protective relative’ and the ‘decisive relative’. The protective relative usually lives with the person with dementia and tends to protect the relationship with the person, conceal carer burden and resist change.…”
Section: Discussionsupporting
confidence: 93%
“…Their perspectives are more in line with those of the professionals involved. This is in line with the work of Clemmensen et al 39 who found differences between the ‘protective relative’ and the ‘decisive relative’. The protective relative usually lives with the person with dementia and tends to protect the relationship with the person, conceal carer burden and resist change.…”
Section: Discussionsupporting
confidence: 93%
“…Being able to recognise your own needs can be argued as being part of a transition process (58). Carers may not have the ability to acknowledge how demanding the situation is to themselves, and they may not be able to recognise their own support needs until they have come to terms with how the dementia disease affect themselves even in the early stages of caring (24,57). In addition, it is paramount that professionals identify carers' support needs in a timely manner, as minor problems may accumulate and spin out of control without carers realising it (57).…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies have a narrow focus on support needs in relation to disease severity of the person cared for. When identifying carers' individual support needs, a more appropriate approach may instead depend on the relationship to the person with dementia (23), and carers own experience of phases due to the challenges of adapting to changes throughout the progression of dementia (24). Allowing a broader focus, a framework to understand different expressions of support needs is defined by four types of needs: felt, normative, comparative and expressed needs (19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive scientific studies of various support programmes show inconsistent results. However, several studies emphasise the importance of access to various forms of support, adapted to families' unique situations (Clemmensen et al, 2019;Strøm and Dreyer, 2019;Tomar et al, 2019).…”
Section: Kontakt / Journal Of Nursing and Social Sciences Related To mentioning
confidence: 99%